An aesthetic study of the sculptural monuments in the Kingdom of Saudi Arabia in the areas of Jubbah and Al-Shuwaymis (Al-Academy, 2025)
This research presents an aesthetic analytical study of the rock-carved sculptural monuments in the areas of Jubbah and Shuwaymis, located in the Hail Region of the Kingdom of Saudi Arabia. These sites are distinguished by a rich collection of symbolic carvings—both anthropomorphic and zoomorphic—executed in relief and intaglio styles, and dating back to various prehistoric periods. The study aims to explore the aesthetic dimensions of these carvings by adopting a descriptive-analytical methodology that highlights their visual and formal qualities. The research is structured into three main chapters: Chapter One outlines the theoretical framework, addressing the geographical context of the two sites and the stylistic characteristics of their rock art; Chapter Two details the research methodology and the analysis of a selected sample of twelve carvings; while Chapter Three presents the findings, which reveal a clear stylistic similarity between the sculptures of Jubbah and Shuwaymis in terms of balanced visual relationships, proportional harmony, and compositional integration. Additionally, the study identifies a contrast between clarity and ambiguity in the forms, along with instances of exaggeration and distortion, suggesting a departure from naturalistic proportionsstrange, and this calls for drawing the recipient’s attention to the surreal design content.